The Implementation of the NHT Type of Cooperative Learning Model to Improve Student’s Activities and Learning Achievement in Basic Techniques for Passing Inner Legs - Siswaya, Ida Bagus Widana (Journal of Education Action Research, 2019)
The purpose of this research was to find out the increase in activity and learning outcomes of basic inner foot passing techniques in students of class X P 2 Singaraja State Vocational High School 2 2018/2019 after the implementation of the NHT Type Cooperative Learning Model. This research is a classroom action research. The subjects in this class action research were students of class X P 2 of Singaraja State Vocational High School 2 of 2018/2019 in 36 people. While the object is activity and the results of learning basic techniques of passing the inner leg. Data on student learning activities are collected by observation sheet, while data on learning outcomes of basic techniques of passing the inner leg are collected by performance tests. Data analysis used in this study used descriptive data analysis. Based on the data analysis carried out it can be concluded that: 1) learning activities of the basic techniques of passing the inner leg increased through the implementation of the NHT type cooperative learning model for students of class XP 2 Singaraja State Vocational High School 2018/2019, and 2) the results of learning basic passing techniques inner leg increases through the implementation of the NHT type cooperative learning model in class XP 2 Singaraja State Vocational High School 2018/2019